Vocational Service Models and Approaches to Improve Job Tenure of People With Severe and Enduring Mental Illness: A Narrative Review - McDowell, Caitlin; Ennals, Priscilla; Fossey, Ellie (Frontiers in Psychiatry, 2021)
Employment is a valued occupation that offers a sense of meaning, identity, and belonging. For people with severe and enduring mental illness, employment has also been associated with personal recovery and decreased use of mental health services. However, this population continues to be underrepresented in the labor market. Sustainable employment is often challenging for people with severe and enduring mental illness, due to a combination of personal, organizational and systemic issues. While Individual Placement and Support is an evidence-based model of employment support known to improve job attainment for people with mental illness, job retention and sustained workforce participation continue to be challenges. This narrative literature review was undertaken to address the question: “What vocational service models and approaches improve job tenure for this population?” CinAHL, Medline, Embase, PsycINFO and Cochrane Library were searched for the period 2005 – 2020, using key terms and subject headings, including “severe mental illness”, “psychiatric disabilit*”, “job tenure” and “job retention”. Several adjunct interventions may enhance job retention, including skills training, cognitive interventions, psychological interventions, and supported education, while social firms offer a different approach focused on creating new, sustainable job opportunities. Peer support and support from family and friends also appear to be important, and emerging evidence suggests that employment specialist practices, technology, self-management, and workplace accommodations may each also influence job tenure. Service providers could make more use of these non-clinical vocational approaches to improve employment retention for people with severe and enduring mental illness.